Modificaciones en el nivel de anión superóxido en leche materna, según la ingesta de flavonoides y carotenoides - Marchesino, Mariana Agostina (2017)
To associate the intake of flavonoids and carotenoids with the breast milk level of superoxide anion, as an oxidative stress marker. Materials and methods. 100 women from Cordoba (Argentina), who breastfed within the first postpartum 6 months, were studied during the 2013- 2015 period, by evaluating their sanitary data, food intake and anion level in milk with multiple logistic regression. Results. The intake of flavonoids, provitamin A carotenoids and nonprovitamin carotenoids was 72 (61) mg/d, 1 813 (1 657) μg/d y 5 427 (3 664) μg/d, respectively. The anion was associated with the intake of flavanols (OR=1.081; CI95 1.001-1.167) y flavanones (OR=1.025; CI95 1.001-1.048). This effect was not seen with other flavonoids and carotenoids. Conclusions. Intake of flavanols and flavanones increases milk oxidation risk, which is relevant to develop diet recommendations.